1993
DOI: 10.2166/wst.1993.0333
|View full text |Cite
|
Sign up to set email alerts
|

Methodological Improvements for the Recovery of B. fragilis Phages and Coliphages from Environmental Samples

Abstract: The effect of different treatments and methods of titration on the recovery of phages infecting Bacteroides fragilis as well as for both somatic and male specific coliphages in environmental samples were evaluated. Recovery of phages infecting B. fragilis is highly dependent on the treatment of the samples. The influence of the treatment in the recovery of coliphages was either null or low. Titration method had some influence on the recovery of phages, mainly those of B.fragilis, from sludge and sediment sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The low removal rate by this pre-treatment showed that it may be a promise biological indicator for drinking water supply. The MPN method appeared to be more sensible than that of PFU as reported previously by Ajaujo et al (1993) and Tartera et al (1988Tartera et al ( , 1992. (1995).…”
Section: Resultssupporting
confidence: 71%
“…The low removal rate by this pre-treatment showed that it may be a promise biological indicator for drinking water supply. The MPN method appeared to be more sensible than that of PFU as reported previously by Ajaujo et al (1993) and Tartera et al (1988Tartera et al ( , 1992. (1995).…”
Section: Resultssupporting
confidence: 71%
“…The sodium pyrophosphate (10 mM) solution (pH 7) used was that described by Danovaro et al (17). The glycine (250 mM) solution (pH 8) used was that described by Araujo et al (2).…”
Section: Methodsmentioning
confidence: 99%
“…(1993) presented a modified analysis for determining the bacterial count in activated sludge solids. The recovery of Bacteroides fragilis from sludge and sediment was improved by treatment with glycine followed by titration (Araujo et al, 1993). More than 90% of copper (II) in aqueous solution was removed by biomass obtained from activated sludge (Nagendra Rao et al, 1993).…”
Section: Sludge Propertiesmentioning
confidence: 99%